CARICA STRUDEL: CULINARY INNOVATION TO STIMULATE SENSORY AND FUN MATHEMATICS ABILITIES IN CHILDREN - Desty Putri Hanifah; Iqbal Bayu; Ahmad Tarikul Majid (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2024)
The study aims to examine the educational impact of introducing Carica Strudel on sensory and mathematical abilities in children aged 4-7 years in Wonosobo. Carica Strudel represents a culinary innovation that combines carica with strudel. It is not only a local culinary dish but also has the potential to serve as an effective learning tool. The research method employed is a descriptive quantitative approach. The research sample consisted of 20 children participating in the